IMPACT OF COVID 19 ON A CONJUGAL RELATIONSHIP (International Journal of Food and Nutritional Sciences, 2022)
The perception of one's partner as welcoming, caring for one's well-being, understanding, and supporting is a crucial element of strong, healthy love partnerships. In other words, they believe their spouses are receptive to their demands. It is more challenging for partners to be sensitive to each other's needs when there are external stressors present, such as unemployment, financial struggle, and work stress. People are more likely to communicate in ways that are excessively critical or contentious when they are under stress from the outside world. Couples and families can endure external stress from epidemics, especially those who are more seriously impacted (such as those who contract the disease, lose their jobs, or suffer significant financial losses). As with any stressor, spouses who are able to communicate more effectively when solving problems, who can be responsive and helpful to their partner, and who are still able to interact positively despite the stress of the epidemic will be more likely to keep their marriages intact. Research on the effects of disasters, which are comparable to epidemics in some ways, suggests that how a disaster affects demographics related to marriage may depend on its nature, even though we know little about how epidemics might affect longer-term outcomes like rates of divorce, marriage, and birth.